Competition with multinational firms: Theory and evidence - Balázs Muraközy; Katheryn Niles Russ (Hungarian Academy of Sciences, Institute of Economics, 2015)
Do multinational firms wield more market power than their domestic counterparts? Using Hungarian firm-level data between 1993 and 2007, we find that markups are 19 percent higher for foreign-owned firms than for domestically owned firms. Moreover, markups for domestically owned firms are significantly lower in industries where multinationals have a greater technological edge, suggesting that Ricardian differences in technology and endogenous markups constitute important dimensions for models of foreign direct investment. We innovate within a canonical Ricardian model of endogenous markups and heterogeneous firms to provide analytical distributions of market shares and markups when goods are imperfect substitutes to provide structure for our empirical analysis. Our model explains about half of the multinational markup premium identified in the empirical analysis.
Keywords: F12; F13; F15; F23; 330; multinational firm; heterogeneous firms; Bertrand competition; multinational firm; heterogeneous firms; Bertrand competition